Empowering Africa's healthcare future: the crucial role of human capital development in bio- and pharmaceutical manufacturing - Michael Mynhardt; Chiluba Mwila; Mahlet K. Habtemariam; Akhona Tshangela; Mar Martinez; Ngashi Ngongo; Jean Kaseya; Nicaise Ndembi (AOSIS, 2023)
Not available.